2015
DOI: 10.1186/s12871-016-0211-4
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine-ketamine versus Dexmedetomidine-midazolam-fentanyl for monitored anesthesia care during chemoport insertion: a Prospective Randomized Study

Abstract: BackgroundDexmedetomidine as a sole agent showed limited use for painful procedures due to its insufficient sedative/analgesic effect, pronounced hemodynamic instability and prolonged recovery. The aim of this study was to compare the effects of dexmedetomidine-ketamine (DK) versus dexmedetomidine-midazolam-fentanyl (DMF) combination on the quality of sedation/analgesia and recovery profiles for monitored anesthesia care (MAC).MethodsFifty six patients undergoing chemoport insertion were randomly assigned to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…Our observation is that the sedation was satisfactory in both study groups, but this was at the expense of the significantly higher ketamine consumption in group M when compared with group D (P < 0.05). The anesthetic sparing effect of intravenous dexmedetomidine was better when compared with intravenous midazolam which was proved in multiple previous studies (Feng et al 2017;Kumari et al 2018), and this was attributed to that dexmedetomidine not only has sedative anixolytic properties but also has also analgesic one (Tosun et al 2006) while midazolam has sedative anixolytic amnesic properties (Koruk et al 2010) and lacks the analgesic one (Chun et al 2016).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Our observation is that the sedation was satisfactory in both study groups, but this was at the expense of the significantly higher ketamine consumption in group M when compared with group D (P < 0.05). The anesthetic sparing effect of intravenous dexmedetomidine was better when compared with intravenous midazolam which was proved in multiple previous studies (Feng et al 2017;Kumari et al 2018), and this was attributed to that dexmedetomidine not only has sedative anixolytic properties but also has also analgesic one (Tosun et al 2006) while midazolam has sedative anixolytic amnesic properties (Koruk et al 2010) and lacks the analgesic one (Chun et al 2016).…”
Section: Discussionmentioning
confidence: 76%
“…Ketamine is an N-methyl-D-aspartate receptor (NMDA) antagonist with sedative, analgesic, and sympathomimetic effects (Miller et al 2011). Among its benefits is the ability to protect airway reflexes with minimal effect on ventilatory drive (Bernard et al 2011), but there are potential problems concerning its use in pediatrics such as emergence delirium (Chun et al 2016). Midazolam is another commonly used intravenous sedative agent with a rapid onset and relatively rapid recovery compared to other benzodiazepines (Chun et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One systemic review study suggested dexmedetomidine exerts potential benefits over midazolam in procedural sedation [10]. However, these sedatives alone often provide insufficient sedative or analgesic effects as well as delayed recovery [11][12][13], for which previous studies suggest a combined sedative/analgesic regimen improve efficacy and safety during endoscopic examination [14][15][16].…”
Section: Introductionmentioning
confidence: 99%